If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3x + -8) = 7(5x + -19) Reorder the terms: 6(-8 + 3x) = 7(5x + -19) (-8 * 6 + 3x * 6) = 7(5x + -19) (-48 + 18x) = 7(5x + -19) Reorder the terms: -48 + 18x = 7(-19 + 5x) -48 + 18x = (-19 * 7 + 5x * 7) -48 + 18x = (-133 + 35x) Solving -48 + 18x = -133 + 35x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35x' to each side of the equation. -48 + 18x + -35x = -133 + 35x + -35x Combine like terms: 18x + -35x = -17x -48 + -17x = -133 + 35x + -35x Combine like terms: 35x + -35x = 0 -48 + -17x = -133 + 0 -48 + -17x = -133 Add '48' to each side of the equation. -48 + 48 + -17x = -133 + 48 Combine like terms: -48 + 48 = 0 0 + -17x = -133 + 48 -17x = -133 + 48 Combine like terms: -133 + 48 = -85 -17x = -85 Divide each side by '-17'. x = 5 Simplifying x = 5
| 3686+67367m=m-686 | | b(b+15)=0 | | 5(2x+7)=9(2x-5) | | y=30000(1+0.14)4 | | 24=.25l+1 | | 2x/5-9=x | | x/5-9=x | | 2x/5-5=x | | y-13=38 | | 2y(2y-9)+(2y-9)= | | 2x/5-5=4 | | 3b^2+6b+3= | | f+43=120 | | 6n+21=4n+1 | | e-35=27 | | 0.000054s= | | d+19=83 | | k^2-36= | | f+27=49 | | 26/100= | | 0.10(y-8)+0.18y=0.12y-0.03(40) | | 3x^2+5x+k= | | 5+d=71 | | I=(1535)(.045)(3) | | 0.50x+0.80(60)=0.25(116) | | -20-40=-21/4 | | -40x+5y=30 | | -40=-21/4(x-20) | | (x-3/2)^2 | | -40=-21/4(x-20 | | x/3+2x/9+4x/27+8x/81+1=x | | 5p+(-6)= |